Enhancing genetic gain through the application of genomic selection in developing irrigated rice for the favorable ecosystem in Bangladesh - Biswas, Partha S.; Ahmed, M. M. Emam; Afrin, Wazifa; Rahman, Anisar; Shalahuddin, A. K. M.; Islam, Rafiqul; Akter, Fahamida; Syed, Md Abu; Sarker, Md Ruhul Amin; Ifterkharuddaula, K. M.; Islam, Mohammad Rafiqul (Frontiers in Genetics, 2023)
The advances in sciences and the uses of advanced technologies in agriculture have made tremendous changes in crop productivity including rice. But the growth of genetic improvement in rice crops is still very low in Bangladesh as in the other South and Southeast Asian rice-growing countries. Breeder’s equation suggests that by increasing the selection differential and decreasing cycle time, the rate of genetic improvement can be accelerated. Selection intensity and selection accuracy are the two crucial factors for increasing selection differential between the parents and their progenies. Creating and capturing higher genetic variance between these populations with high selection intensity together with higher accuracy within the shortest possible time is the prerequisite for enhancing genetic gain for any trait. Comprehensive yield testing at multi-locations at early generations together with the shortest line fixation time can expedite the rapid recycling of parents in the breeding program through recurrent selection. Genomic selection is efficient in capturing high breeding value individuals taking additive genetic effects of all genes into account with and without extensive field testing, thus reducing breeding cycle time enhances genetic gain. In the Bangladesh Rice Research Institute, GS technology together with the trait-specific marker-assisted selection at the early generation of RGA-derived breeding lines showed a prediction accuracy of 0.454 to 0.701 with 0.989 to 2.623 relative efficiency over the four consecutive years of exercise. This study reports that the application of GS together with trait-specific MAS has expedited the yield improvement by around seven-fold over the baseline annual genetic gain and shortened the breeding cycle by around 1.5 years from the existing 4.5 years